KREACJA PODMIOTU EPISTOLARNEGO W KORESPONDENCJI WISŁAWY SZYMBORSKIEJ Z KORNELEM FILIPOWICZEM I ZBIGNIEWEM HERBERTEM - Sitarczuk, Marta (Colloquia Litteraria, 2025)
The letters exchanged by Wisława Szymborska with Kornel Filipowicz, on the one hand, and with Zbigniew Herbert, on the other, imply a host of interesting questions, which have inspired this essay. A brief description of the concept of letter proposed Kreacja podmiotu epistolarnego … by Anita Całek is followed by an analysis of Wisława Szymborska’s correspondence with Kornel Filipowicz and Zbigniew Herbert, with a focus on the way in which these authors create their respective epistolary subjects. Two levels of such subject creation have been identified—related, respectively, to real and fictitious figures, the latter ones coming to being in these very letters. Discussed are the similarities and differences between Szymborska’s letters to/from Filipowicz and Herbert, and the conclusions stemming from the proposed analysis are put forth.